Sino‐Himalayan mountains act as cradles of diversity and immigration centres in the diversification of parrotbills (Paradoxornithidae). (11th March 2016) - Liu, Yang; Hu, Junhua; Li, Shou‐Hsien; Duchen, Pablo; Wegmann, Daniel; Schweizer, Manuel
Abstract: Aim: Montane regions like the Sino‐Himalayas constitute global diversity hotspots. Various mechanisms such as in situ adaptive divergence, speciation following immigration or allopatric diversification in complex landscapes have been proposed to account for the exceptional diversity found in a particular clade in a montane setting. We investigated macroevolutionary patterns to test these different hypotheses in the continental radiation of a Sino‐Himalayan bird group, the parrotbills (Paradoxornithidae). Location: Sino‐Himalayan region, Indo‐Burma. Methods: We used phylogenetic comparative methods based on a multilocus, time‐calibrated phylogeny to reconstruct patterns of lineage diversification, biogeographical history, morphological evolution as well as of climate niche history using ecological niche modelling. Results: The radiation of parrotbills started c.  12 Ma, diversifying at an apparent constant rate over time. The biogeographical history appears to be complex, within‐region speciation in mountains was restricted to China. Size evolution was concentrated in the early phase of parrotbill radiation, whereas morphological shape evolution did not differ from Brownian motion. We found no indication for niche conservatism, with climate niche evolution occurring throughout the radiation of parrotbills. Conclusions: Parrotbills diversified within a time span of increased regional orogenesis and associated strong climate change. While the south‐west and central Chinese mountains were revealed to be a species pump, with in situ allopatric diversification triggered by complex topography and high habitat turnover, the diversity in the Himalayas was chiefly the result of immigration. Evidence for continuous ecological specialization and for the absence of climate niche conservatism could be interpreted as the consequence of ongoing climate‐ and habitat‐induced ecological opportunities. The radiation of parrotbills demonstrates the influence of multiple drivers of diversification in a single group due to the dynamic geological and palaeoclimatic history of the Sino‐Himalayan region and illustrates the complex nature of continental radiations.